Expression of Endoglin and Vascular Endothelial Growth Factor as Prognostic Markers in Experimental Colorectal Cancer - Ilhan, Nevin; Gungor, Hilal; Gul, H. Fatih; Eroksuz, Hatice (Int Inst Anticancer Research, 2016)
Background/Aim: Endoglin (CD105) is a receptor for the transforming growth factor-beta 1 (TGF beta 1) with crucial role in vascular development and angiogenesis. Additionally, vascular endothelial growth factor (VEGF) overexpression has been associated with advanced stage and poor survival for several cancer types. These molecules have been shown to be useful markers for identifying proliferating endothelium involved in tumor angiogenesis, especially in patients with cancer at risk of developing metastases. The aim of this study was to evaluate the relationship between VEGF and endoglin expression in an experimental model of colorectal cancer, as well as to investigate the effect of cyclooxygenase-2 (COX2) inhibitors on tumor development incidence. Materials and Methods: Colon cancer was induced with 1,2-dimethylhydrazine dihydrochloride (DMH). Celecoxib and diclofenac treatment was started simultaneously with DMH induction. Endoglin protein expression was performed using western blot analysis. VEGF plasma concentrations were measured by enzyme-linked immunosorbent assay. Results: In histopathological evaluations, no pathological change was observed in control rats, while adenocarcinoma (62.5%), dysplasia (31.25%) and inflammation (6.25%) were detected in the group given DMH. In treatment groups, a marked decrease was observed in adenocarcinoma rate. Expression of endoglin protein was significantly elevated in the DMH group compared to controls (p<0.001). No statistically significant difference was noted between treatment groups and DMH group regarding endoglin expression but a decrease was detected in the celecoxib-treated groups. Conclusion: It was confirmed by histopathology and western blotting that COX2 inhibitors, particularly celecoxib, decrease the rate of disease and slow-down progression of existing CRC. These data show that endoglin expression may have an important role in tumor angiogenesis and predict of tumor invasion.
Keywords: Colorectal cancer; angiogenesis; endoglin; VEGF; COX-2 inhibitors